Variables at the Community Health Center Have the Ecological Effect on the Performance of Health Workers: A Multilevel Evidence from Klaten, Central Java - Handayani, Nia; Tamtomo, Didik Gunawan; Murti, Bhisma (Journal of Health Policy and Management, 2020)
Background:Performance is a work achievement that can be achieved from a job. Employee performance in an organization leads to the ability of employees to complete all tasks that have become their responsibility. Various problems in the workplace can often cause work stress, if it lasts long can cause various disturbances. Success in achieving goals is supported by the role of a leader with the leadership style used. This study aimed to examine the effects of work stress and leadership style on the performance of public health workers.Subjects and Method:This was a cross sectional study conducted at the Klaten District Health Center, Central Java, from November to December, 2019. A sample of 200 health workers was selected by stratified random sampling. The dependent variable was work performance. The independent variables were work stress, leadership style, education, tenure, and type of work. The data were collected by questionnaire and analyzed by a multilevel logistic regression run on Stata 13.Results: Performance of health workers decreased with heavy work stress (b= -1.65; 95% CI= -2.58 to -0.72; p= 0.001). Performance of health workers increased with democratic leadership style (b= 1.40; 95% CI= 0.44 to 2.36; p = 0.004), high education level (b= 1.58; 95% CI= 0.65 to 2.52; p= 0.001), tenure ≥6 years (b= 1.72; 95% CI= 0.73 to 2.70; p= 0.001), and type of work without any additions (b= 2.05; 95% CI= 1.07 to 3.03; p<0.001). Community health center had ecological effect on performance of health workers with ICC= 12.74%.Conclusion: Performance of health workers decreases with heavy work stress. Performance of health workers increases with democratic leadership style, high education level, tenure ≥6 years, and type of work without any additions. Community health center has ecological effect on performance of health workers.Keywords:work performance, work stress, leadership style, community health centerCorrespondence: Nia Handayani. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: niahandayani19@gmail.com. Mobile: +6282133055176.Journal of Health Policy and Management (2020), 5(2): 152-161https://doi.org/10.26911/thejhpm.2020.05.02.08